Protest Movements in Asylum and Deportation - Rosenberger, Sieglinde; Stern, Verena; Merhaut, Nina; Rosenberger, Sieglinde; Stern, Verena; Merhaut, Nina (Cham Springer Nature, 2018)
Protest mobilization and outcome; Political participation; Emotions and social ties; Deportation nation; Refugees; Pro-migrant protest; Anti-migrant protest
English
Keywords: Development studies; Protest mobilization and outcome; Political participation; Emotions and social ties; Deportation nation; Refugees; Pro-migrant protest; Anti-migrant protest